2020
DOI: 10.3390/ijerph17114000
|View full text |Cite
|
Sign up to set email alerts
|

Space-Time Surveillance of Negative Emotions after Consecutive Terrorist Attacks in London

Abstract: Terrorist attacks pose significant threats to mental health. There is dearth information about the impact of consecutive terrorist attacks on space-time concentrations of emotional reactions. This study collected (1) Twitter data following the two terrorist attacks in London in March and June of 2017, respectively, and (2) deprivation data at small areal levels in the United Kingdom. The space-time permutation model was used to detect the significant clusters of negative emotions, including fear, sadness, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 60 publications
(98 reference statements)
0
8
0
Order By: Relevance
“…In the context of natural disasters, several studies have shown that geographically concentrated negative emotions could be identified before, during, and after a disaster with the help of Twitter data [ 14 , 24 , 34 , 44 ]. In our study, we focused on negative emotions and examined them individually and as a variable of all negative emotions in all time periods.…”
Section: Discussionmentioning
confidence: 99%
“…In the context of natural disasters, several studies have shown that geographically concentrated negative emotions could be identified before, during, and after a disaster with the help of Twitter data [ 14 , 24 , 34 , 44 ]. In our study, we focused on negative emotions and examined them individually and as a variable of all negative emotions in all time periods.…”
Section: Discussionmentioning
confidence: 99%
“…In such studies, sentiment analysis is generally carried out on geotagged tweets to provide an overview about the overall mood of the population at different regions or cities [ 10 ]. Other studies focused on identifying user sentiment during or after a particular event (such as a pandemic [ 11 , 12 ] or terrorism event [ 13 ]) or analyzed user sentiment at different geographical areas with the aim of investigating the mobility patterns of people within a city [ 14 ]. In a number of these studies, data about the sentiment of the tweets themselves were correlated with various metrics affecting urban living (such as job opportunities and access to public transportation) to provide insight into the effect these measures have on the happiness of the population [ 15 ].…”
Section: Related Researchmentioning
confidence: 99%
“…In another example, geotagged tweets were classified based on emotional dimensions such as pleasantness and dominance, the results of which were visualized over the world map to show emotional trends across different countries [ 19 ]. Other studies used geotagged tweets to analyze the emotions of people (fear, sadness, sympathy) in response to particular events such as the London Westminster and London Bridge attacks [ 13 ] and the Paris attacks (anger and sadness) [ 20 ].…”
Section: Related Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…A large quantity of social media data makes it possible to detect emergency events or the status of an assembled crowd. Leveraging social media big data for emergency response and disaster management has attracted considerable attention [ 16 , 17 , 18 ]. Social media data associated with temporal and geographical information can reveal human behavior patterns [ 19 , 20 , 21 ], and human emotion changes can be reflected by social media content [ 22 , 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%